Associations between naples prognostic score and stroke and mortality among older adults - Junting Song; Lin Yin (European Journal of Medical Research)
Abstract Background Inflammation and malnutrition in the body are closely related to the incidence of stroke. Older adults often suffer from malnutrition and inflammation. Naples Prognostic Score (NPS), a novel inflammation-malnutrition score, can effectively assess the inflammation and nutritional status of the body. The aim of this study is to explore the connection between NPS and stroke among older adults, as well as the association between NPS and mortality in older adults. Methods Participants eligible for the study were collected from National Health and Nutrition Examination Survey(NHANES) data from 1999 to 2018. Logistic regression models were employed to investigate the link between NPS and stroke. Additionally, restricted cubic spline was utilized to explore the correlations. Subgroup analysis was adopted in order to ensure the credibility of the results. Kaplan–Meier Survival curve and cox regression models and were utilized to evaluate the link between NPS and mortality among older adults. Results 16,940 older adults qualified for analysis. The participants with stroke had higher levels of NPS. In the logistic regression model, NPS was positively related to stroke (high NPS vs. low NPS, OR = 1.70 (95% CI 1.24–2.35), P < 0.001). Restricted cubic spline revealed a positive non-linear relationship (P for overall < 0.001, P for non-linear < 0.001). Subgroup analysis showed that the association between NPS and the incidence of stroke is more significant in the non-diabetes population (P < 0.001). The Kaplan–Meier curve shows that patients with high NPS have a significantly higher risk of all-cause mortality and cardiovascular mortality (P < 0.001). In the Cox regression model, a positive correlation was observed between NPS and mortality among older adults (all-cause mortality: HR = 1.36 (95% CI 1.30–1.42); cardiovascular mortality:HR = 1.59 (95% CI 1.45–1.75)). Conclusions A positive link was observed between NPS and stroke and mortality. Routine NPS screening may enhance risk stratification in geriatric clinics.